Analisis Pengelolaan Arsip PT XYZ - Fina Novita Sari Simanjuntak; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
One element of this administrative activity is information storage and document storage activities known as archives. As a recorder of information from all organizational activities, archives function as a memory center, decision support, proof of the existence of the organization, and for other organizational purposes. Considering the very important function archives, then there must be good and correct archive management. Important letters and documents in an organization, both government and private, of course require an archiving process,In archive management, there are several archival jobs or activities, an archive management system needs to be implemented to facilitate the storage and retrieval of archives whenever needed quickly and precisely, so it is necessary to determine the storage method.The purpose of this research is to find out what the archive storage system is at PT XYZ to find out what problems or obstacles are being faced and experienced. The population in this study were 4 employees who already had a lot of experience at PT XYZ .The research method used in this research is a qualitative descriptive method. Researchers used interviews and also distributed questionnaires to employees to get actual data. PT XYZ has done the archiving quite well but there are still obstacles and challenges in archiving. This problem also occurs due to a lack of manpower for the archiving process.